Are gun ownership rates and regulations associated with firearm incidents in American schools? A forty-year analysis (1980–2019). (September 2021) - Hamlin, Daniel
Abstract: Purpose: This study examines the relationship between state gun ownership rates and school firearm incidents ( n  = 1275) and injured/killed victims ( n  = 2026) of these incidents over a forty-year period (1980–2019). It also investigates whether child access prevention, minimum age requirements for gun purchases, and mandatory gun safety training laws are associated with fewer school firearm incidents and injured/killed victims. Methods: Data were linked together from the School Shootings Database, State Firearm Law Database, the National Center for Education Statistics, and the US Census Bureau. State fixed effects and interrupted time series analyses were performed. Results: State gun ownership rates declined between 1980 and 2019 while school firearm incidents generally ranged between 20 and 40 incidents before skyrocketing to 102 incidents in 2018 and 110 incidents in 2019. Findings were mixed on the relationship between state gun ownership rates and school firearm incidents and injured/killed victims. Additionally, child access prevention, minimum age requirements for gun purchases, and mandatory gun safety training laws exhibited weak and inconsistent relationships with school firearm incidents. Discussion: Although access to firearms plays an undeniable role in school shootings, it remains unclear what policies are needed to reduce these incidents. Future research may be needed to explore holistic approaches to addressing this problem. Highlights: School firearm incidents ranged between 20 and 40 incidents before skyrocketing to over 100 incidents in 2018 and 2019. Findings were mixed on the relationship between state gun ownership rates and school firearm incidents. Gun regulations exhibited weak and inconsistent associations with school firearm incidents and injured/killed victims. Future research may be needed to explore holistic approaches to addressing the problem of gun violence in American schools.